THE ROLE OF TECHNOLOGY IN DIGITAL ERA LEARNING: OPPORTUNITIES AND CHALLENGES - Hasanah, Nur Faidatul; Lubis, Ahmad Hafidz Lubis (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze the role of technology in learning in the digital era with the object of teachers. The research method used in this study is qualitative research method with literature study. This study reports three important data themes that include the ability to utilize technology in learning, opportunities in developing learning using technology in the digital era and challenges faced in utilizing technology. In doing so, the researcher investigated how to overcome challenges and capitalize on opportunities to improve the quality of education in the digital era. By combining innovative approaches to teaching, teacher professional development, the use of technology in digital learning becomes a bridge for teachers and students in the development of learning in the digital era